CHARACTER DEVELOPMENT OF CLASS 3 STUDENTS AT SDN 091320 RAYA TONGAH THROUGH APPRECIATION OF FABLES LITERATURE WORKS - O Tambunan, Jubelando; O. Brusa, Jorge; ur Asima Sidabutar, Melisa; Jusnita Samosir, Herna; Samosir, Alexander; usnita Samosir, Herna (Universitas Efarina, 2021)
The national education functions as a custodian of values in society so that they can be preserved. The character building is a filter for negativity in globalization. To instill the value of character education, of course it is not enough just to be given memorization or test scores that meet the passing standards, but as a whole it must be integrated between cognitive, affective and psychomotor. In this study, researchers examined the character improvement of grade 3 students at SDN 01320 Raya Tongah in appreciating fable literary works. The story fable is an animal that teaches various grade 3 elementary schools. The fable contains values that are acceptable to students. There are many learning values that can be explored in the fable which can then be used as an alternative in educating students. The purpose of this research is to show what character education values can be taken in the fable and to describe how the character reporting of 3rd grade students of SDN 091320 Raya Tongah through the appreciation of fable literary works. This type of research is conducted in qualitative research. The results of this study indicate that the character values in the fable that can be a role model for SDN 091320 students include: honest attitude, responsibility attitude as well as an attitude of wanting to help and character building of SDN 091320 Raya Tongah through the appreciation of fable literature. The story book approach, good communication, and implementation, namely by inviting students to appear properly and the teacher inviting students to apply what they got from the fable stories they had created together.